Targeted therapy of anaplastic thyroid cancer - P. A. Nikiforovich; A. P. Polyakov; I. V. Sleptsov; N. S. Boyko; Yu. A. Gronskaya; N. I. Timofeeva; R. A. Chernikov (Опухоли головы и шеи)
Introduction. Anaplastic thyroid cancer (ATC) is a very rare malignant tumor of the thyroid comprising 1–2 % of all thyroid cancers. In this pathology, response rate for standard systemic therapy is less than 15 %, and long-term results remain unsatisfactory. Additionally, there are no data conclusively showing that cytotoxic chemotherapy improves survival or quality of life in patients with ATC.Aim. To improve the results of treatment of patients with ATC through evaluation of the effectiveness of targeted therapy in cases of BRAFV600E mutation.Materials and methods. The multicenter prospective study included 29 patients with ATC IVB–C, T4a–bN1a–bM0–1. The patients were divided into 2 groups. The Group 1 (control) included 15 patients with resectable / nonresectable, metastatic / nonmetastatic ATC (without BRAFV600E mutation), stages IVB–C who received standard types of treatment (surgical intervention, radiation, and chemotherapy). The Group 2 consisted of 14 patients with nonresectable or metastatic ATC, stages IVB–C, who received combination therapy (surgical intervention, radiation, and chemotherapy) with inclusion of inhibitors of BRAF dabrafenib and trametinib in neoadjuvant and adjuvant regimens.Results. The study showed the effectiveness of targeted therapy with inhibitors of BRAF mutations in treatment of locally advanced non-operable metastatic ATC with BRAFV600E mutation. Overall response (complete response + partial response) in the Group 1 was 0 %, in the Group 2 it was 64 %. Therefore, treatment scheme dabrafenib + trametinib is a prmising approach to combination targeted therapy in patients with ATC and BRAFV600E mutation. Conclusion. Dabrafenib + trametinib is a promising combination targeted therapy option for patients with ATC with a BRAFV600 mutation demonstrates a high overall response rate, a prolonged duration of response, and an increase in survival rates with controlled toxicity.